Overlapping Oppositions in Beowulf, Guthlac A, and the Old English Physiologus - Roop, Mary Nicole (My University, 2016)
Binaries in literature depict people, ideas, and actions that are in opposition to each other: good and evil; life and death; hero and villain. These pairings appear in multiple ways and places throughout much of literary history. During the Anglo-Saxon period, binary opposition was especially important for portraying not only opposition between Christianity and pre-existing religions, but also for illustrating how important concepts like the Anglo-Saxon warband were used to tie old and new ways of thinking together. However, literature in the Middle Ages also shows the presence of slippage— places where oppositional structures or characters show conflicting similarities when they should not—i.e., a hero murders someone in cold blood. In fact, imperfect oppositional binaries abound in medieval texts. However, such moments of slippage may not have always sat well with the Anglo-Saxon people, as in some traditions, certain similarities between symbols of good and evil would conflict with their beliefs. As a result, medieval literary binaries often exhibit multiple layers of slippage as a result of the blending and combining of divergent traditions characteristic of the period. This thesis will examine the layers within such binaries and explore the effect of overlapping and conflicting traditions on pre-existing binaries across multiple instances in Old English literature.
Chapter I: INTRODUCTION - 1 Chapter II: “MONSTERS OF MEN: BINARIES IN BEOWULF” - 16 Chapter III: “SAINTLY SLIPPAGE: GUTHLAC A AND THE HEROIC SAINT” - 37 Chapter IV: “BEASTLY BINARIES: ANIMAL SYMBOLISM IN OLD ENGLISH POETRY” - 52 Chapter V: CONCLUSION - 66 REFERENCES - 76
Keywords: Theses; English